2001
DOI: 10.1111/j.1469-7793.2001.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for metaboreceptor stimulation of sweating in normothermic and heat‐stressed humans

Abstract: Increases in sweating during heat stress occur secondarily to increases in internal and skin temperatures. In addition to these thermal factors, non-thermal factors, such as central command, muscle mechano/metaboreceptor activation and baroreflexes, have been shown to modulate sweating during whole-body heating and during exercise (Van Beaumont & Bullard, 1963;Solack et al. 1985;Mack, 1995;Yamazaki et al. 1996;Kondo et al. 1999;Kondo, 2001). However, independent roles of these non-thermal factors in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 21 publications
6
86
1
1
Order By: Relevance
“…However, it has been reported that skin sympathetic nerve activity and SR are not altered by phenylephrine-administered increases in arterial blood pressure during mild heating (46). Furthermore, the SR remained elevated during activation of the muscle metaboreceptors, even after MAP returned to baseline levels, with administration of sodium nitroprusside (38). These results suggest that the arterial baroreflex does not influence the sweating response.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, it has been reported that skin sympathetic nerve activity and SR are not altered by phenylephrine-administered increases in arterial blood pressure during mild heating (46). Furthermore, the SR remained elevated during activation of the muscle metaboreceptors, even after MAP returned to baseline levels, with administration of sodium nitroprusside (38). These results suggest that the arterial baroreflex does not influence the sweating response.…”
Section: Discussionmentioning
confidence: 46%
“…It is well known that group III muscle afferents are stimulated predominantly by mechanically sensitive muscle mechanoreceptors, whereas group IV muscle afferents are stimulated mainly by chemically sensitive muscle metaboreceptors. Activation of muscle metaboreceptors by postexercise muscle ischemia (PEMI) under normothermic and mildly hot conditions induces sweating (2,4,22,38). Additionally, Kondo et al (23) reported that activating the muscle mechanoreceptors by passive limb movement for 2 min evoked slight sweating under hot conditions.…”
mentioning
confidence: 99%
“…heat stress; thermoregulation; isometric handgrip exercise; postexercise ischemia EXTENSIVE STUDIES HAVE SHOWN that mechano-and baroreceptors (cardiopulmonary and arterial) modulate the heat loss responses of cutaneous vasodilation and sweating during passive heating, exercise, and postexercise recovery, while central command can influence sweating and cutaneous vasodilation during exercise (12,13,23,24,31,34). In contrast, information regarding the influence of metaboreceptors on thermoeffector activity during and following exercise remains limited, largely because of the difficulties associated with isolating the muscle metaboreflex.Much of our understanding of the influence of metaboreceptor activity on heat loss responses has been limited to findings obtained using an isometric handgrip (IHG) exercise model (18,20,30). After an IHG exercise bout at a given percentage of maximal voluntary contraction (MVC), a 2-min period of ischemia is induced by occlusion of all limb blood flow to the exercising arm, which is thought to trigger group III and IV chemosensitive afferents (26).…”
mentioning
confidence: 99%
“…Much of our understanding of the influence of metaboreceptor activity on heat loss responses has been limited to findings obtained using an isometric handgrip (IHG) exercise model (18,20,30). After an IHG exercise bout at a given percentage of maximal voluntary contraction (MVC), a 2-min period of ischemia is induced by occlusion of all limb blood flow to the exercising arm, which is thought to trigger group III and IV chemosensitive afferents (26).…”
mentioning
confidence: 99%
“…increases heart rate, mean arterial pressure, sweating rate, and sympathetic nerve activity to skin and muscle [Nishiyasu et al, 1994;Rowell & O'Leary, 1990;Saito et al, 1990;Shibasaki et al, 2001;Vissing et al, 1991]. These physiological responses associated with the IHG are related to mechanisms involving central command such as stimulation from the parallel activation of motor and autonomic pathways and the activation of mechanosensitive or metabosensitive receptors in exercising muscle [Crandall et al, , 1998Kondo et al, 1998Kondo et al, ,1999Rowell & O'Leary, 1990].…”
Section: Effect Of Exercise Intensity On the Ihg-mediated Response Ofmentioning
confidence: 99%